2021
DOI: 10.1007/s10479-021-03961-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing a sustainable closed-loop pharmaceutical supply chain in a competitive market considering demand uncertainty, manufacturer’s brand and waste management

Abstract: Pharmaceutical supply chain (PSC) is one of the most important healthcare supply chains and the recent pandemic (COVID-19) has completely proved it. Also, the environmental and social impacts of PSCs are undeniable due to the daily entrance of a large amount of pharmaceutical waste into the environment. However, studies on closed-loop PSCs (CLPSC) are rarely considered real-world requirements such as competition among diverse brands of manufacturers, the dependency of customers’ demand on products’ price and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Campos proposed that management, information technology, and infrastructure are key in the medicine return process [ 16 ]. Some studies have explored the social responsibility of pharmaceutical enterprises in the closed-loop operation of medicine return and manufacturing [ 17 ], the economic benefits of medicine return and reuse to the pharmaceutical supply chain [ 18 , 19 ], and the planning of logistics for medicine return from hospitals [ 20 ]. However, there are few studies on residents’ proper return behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Campos proposed that management, information technology, and infrastructure are key in the medicine return process [ 16 ]. Some studies have explored the social responsibility of pharmaceutical enterprises in the closed-loop operation of medicine return and manufacturing [ 17 ], the economic benefits of medicine return and reuse to the pharmaceutical supply chain [ 18 , 19 ], and the planning of logistics for medicine return from hospitals [ 20 ]. However, there are few studies on residents’ proper return behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of helpful research studies can be found in the literature, concentrating on CLSCN design (e.g., see Polo et al, 2019 ; Sazvar et al, 2021 ). However, in this section, the most relevant studies related to the supply chain of medical items are reviewed in brief.…”
Section: Survey On the Related Workmentioning
confidence: 99%
“…Wang et al [13][14][15][16][17][18][19] studies the decision-making of CLSC under different conditions, such as corporate social responsibility, revenue sharing, retail competition, manufactory competition and so on. Sazvar et al [20][21][22][23][24][25][26] apply CLSC to specific industries and make optimal decisions in actual life. Research scope involves Pharmaceutical supply chain, seafood, vehicle, and so on.…”
Section: Literature Reviewmentioning
confidence: 99%